Wilsey and Helmick, Morris County - Adam, Janet (Kansas State University, The Chapman Center for Rural Studies, 2012)
The author used an accumulation of fragmented information collected from local contacts and historic documents to create a comparison between the twin towns of Wilsey and Helmick, Morris County, Kansas. She used census reports, plat maps, statistical data, personal interviews, taped interviews and information from local historians to piece together the history of these twin towns.
Janet Adam, “Wilsey and Helmick, Morris County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/93.
Keywords: Morris County; Wilsey; Helmick; Missouri Pacific Railroad; Council Grove; Matson Ottis